Escalated Alcohol Self-Administration and Sensitivity to Yohimbine-Induced Reinstatement in Alcohol Preferring Rats: Potential Role of Neurokinin-1 Receptors in the Amygdala. (10th August 2019) - Nelson, Britta S.; Fulenwider, Hannah D.; Nennig, Sadie E.; Smith, Britessia M.; Sequeira, Michelle K.; Chimberoff, Scott H.; Richie, Christopher T.; Cheng, Kejun; Rice, Kenner C.; Harvey, Brandon K.; Heilig, Markus; Schank, Jesse R.
Abstract: Genetic factors significantly contribute to the risk for developing alcoholism. To study these factors and other associated phenotypes, rodent lines have been developed using selective breeding for high alcohol preference. One of these models, the alcohol preferring (P) rat, has been used in hundreds of preclinical studies over the last few decades. However, very few studies have examined relapse-like behavior in this rat strain. In this study, we used operant self-administration and yohimbine-induced reinstatement models to examine relapse-like behavior in P rats. Our previous work has demonstrated that P rats show increased expression of the neurokinin-1 receptor (NK1R) in the central nucleus of the amygdala (CeA), and this functionally contributes to escalated alcohol consumption in this strain. We hypothesized that P rats would show increased sensitivity to yohimbine-induced reinstatement that is also mediated by NK1R in the CeA. Using Fos staining, site-specific infusion of NK1R antagonist, and viral vector overexpression, we examined the influence of NK1R on the sensitivity to yohimbine-induced reinstatement of alcohol seeking. We found that P rats displayed increased sensitivity to yohimbine-induced reinstatement as well as increased neuronal activation in the CeA after yohimbine injection compared to the control Wistar strain. Intra-CeA infusion of NK1R antagonist attenuates yohimbine-induced reinstatement in P rats. Conversely, upregulation of NK1R within the CeA of Wistar rats increases alcohol consumption and sensitivity to yohimbine-induced reinstatement. These findings suggest that NK1R upregulation in the CeA contributes to multiple alcohol-related phenotypes in the P rat, including alcohol consumption and sensitivity to relapse. Highlights: P rats show elevated sensitivity to yohimbine-induced reinstatement of alcohol seeking. Yohimbine-induced Fos activation in the central amygdala is also elevated in the P rat strain. Infusion of a NK1R antagonist into the central amygdala attenuates yohimbine-induced reinstatement in P rats. NK1R overexpression in the central amygdala of control rats increases sensitivity to yohimbine-induced reinstatement.